THE EFFECT OF AXIAL AND RADIAL DIRECTIONS ON THE EXTRACTIVE CONTENT OF LONTAR (BORASSUS FLABBELLIFER) STEM FROM WONRELI VILLAGE - Hanny R Rupidara; Herman Siruru; Lieke Tan (Jurnal Sylva Scienteae, 2023)
Community interest in timber forest products is still high, but log production is decreasing. This can be circumvented by using non-timber forest products, but it is necessary to test the extractive content first so that the utilization is maximized. The purpose of this study was to determine the effect of the axial and radial directions on the extractive content of lontar (Borassus flabbellifer) stem. Extractive content testing was preceded by making particles from lontar stems. Then the lontar stem particles were dried and powdered with a size of 40 mesh and retained at 60 mesh. The content of cold water-soluble extractives was analyzed using the TAPPI T 207 om-88 standard, the hot water-soluble extractives content using the TAPPI T 264 om-88 standard and the ethanol-benzene soluble extractives content using TAPPI T 257 cm-85. The results showed that the levels of cold-water soluble extractives ranged from 1.426 - 8.159%, hot water-soluble extractives 1.854 - 10.07% and ethanol-benzene soluble extractives 1.97% - 10.11%. The correlation between hot water-soluble extractives and cold-water soluble extractives is 0.8390 and 0.6325 for ethanol-benzene soluble extractives, while the correlation between cold water-soluble extractives and ethanol-benzene soluble extractives is 0.2954